Isolated Cerebral Mucormycosis in Immunocompetent Adults who Inject Drugs: Case Reports and Systematic Review of the Literature. (13th November 2020) - Meyerowitz, Eric A; Sanchez, Sarimer; Mansour, Michael K; Triant, Virginia A; Goldberg, Marcia B
Abstract: Background: Mucormycosis involves life-threatening rapidly progressive angioinvasion with infiltration across tissue planes, resulting in necrosis and thrombosis, most commonly seen in the setting of immunocompromised states. We describe 2 cases of isolated cerebral mucormycosis in immunocompetent adults and describe this syndrome in detail in the context of a systemic literature review. Methods: Using the criteria (1) isolated cerebral disease, (2) mucormycosis (by polymerase chain reaction, culture, or pathology), and (3) affected an immunocompetent individual, we identified 53 additional cases from 1969 to 2020. Results: Of these 55 cases, ~60% occurred in men, >70% were in patients under age 35, 92% were associated with intravenous drug use, and >85% had infection centered in the basal ganglia. Many presented with cranial nerve deficits, headache, focal weakness, or altered mental status. Conclusions: No patient survived without amphotericin, and steroid administration was associated with worse outcomes. Given the current opioid crisis, this syndrome may be seen more frequently.